New Paleointensity Data Suggest Possible Phanerozoic-Type Paleomagnetic Variations in the Precambrian - Lloyd, S.J.; Biggin, A.J.; Li, Zheng-Xiang (AMER GEOPHYSICAL UNION, 2021)
The state of the geomagnetic field throughout the Precambrian era is largely unknown. Approximately 8% of global paleointensity records account for ∼4 billion years of Earth history. Despite this severe sparsity, the data are used to constrain models that predict the timing of significant deep earth events such as inner core nucleation. This carries with it the assumption that the Precambrian paleomagnetic field was less variable when compared to the Phanerozoic, or at least that the sparse data can be averaged to accurately represent a particular time period. This study reports new paleointensities from the West Australian Craton at 755 Ma (the Mundine Wells dyke swarm) and 1,070 Ma (the Bangemall Sills); both of which occurred within ∼30 Ma from times at which extremely weak and anomalously strong fields, respectively, have been reported. Virtual dipole moments of 6.3 ± 0.1 Am2 × 1022 and 1.8 ± 1.2 Am2 × 1022 have been obtained from the two suites of mafic rock units which are substantially different to the previous measurements for the two respective ages. The findings suggest that field variability over tens of Myrs in the Precambrian was greater than has previously been assumed. This is supported by comparisons of paleosecular variation and distributions of virtual dipole moments. If variability in the Precambrian field is similar to that observed in the Phanerozoic, spatial or temporal anomalies may introduce significant bias to statistical analyses and model constraints, implying that caution should be employed in the interpretation of the Precambrian dipole moment records.